The Effect of Entrepreneurship and Mental Accounting in Enhancing Business Sustainability: A Financial Performance Mediation Model - Siti Arifah; Emma Dwi Ratnasari; Jalu Aji Prakoso; Rochmat Aldy Purnomo; Rindang Widuri; M. Rudianto (Institut Bisnis dan Informatika Kesatuan, 2026)
This study aims to analyze the financial performance of MSMEs in Magelang City, Central Java, examine the effect of entrepreneurship and mental accounting as initial capital in achieving business sustainability, and formulate strategies for the sustainable development of MSMEs. A mixed-method approach was used, utilizing targeted surveys of MSME actors to collect quantitative data, which was then analyzed using Partial Least Squares (PLS) through SmartPLS software. Qualitative data were collected from in-depth interviews and Focus Group Discussions (FGDs) to capture the experiences and challenges faced by MSMEs. The results of the study indicate that the financial performance of MSMEs is still suboptimal despite government initiatives, such as the ‘UMKM Naik Kelas’ (MSME Upgrading) programme. Entrepreneurship and mental accounting have a significant influence on business sustainability, particularly in financial management and decision-making. Research on strengthening business sustainability through the role of entrepreneurship and mental accounting in financial performance is often constrained by the subjective nature of the variables, the limited availability of financial data, and the dynamic business environment. Strengthening these two aspects significantly increases the likelihood that MSMEs will not only survive but also grow and achieve optimal financial performance.